NF-κB signaling activation via increases in BRD2 and BRD4 confers resistance to the bromodomain inhibitor I-BET151 in U937 cells. (November 2018) - Hishiki, Kotaro; Akiyama, Masaharu; Kanegae, Yumi; Ozaki, Koji; Ohta, Miyuki; Tsuchitani, Emi; Kaito, Ken; Yamada, Hisashi
Highlights: BRD2 and BRD4 were increased in I-BET151-resistant U937 (U937R) cells. Constitutive activation of the NF-κB signaling pathway was induced in U937R cells. IKK inhibitor VII restored the sensitivity to I-BET151 in U937R cells. IKK inhibitor VII synergistically enhanced the antitumor activity of I-BET151. Abstract: Novel epigenetic therapies targeting bromodomain and extra-terminal (BET) family proteins have shown therapeutic efficacy in diverse hematologic malignancies and solid cancers. However, the mechanism of resistance remains poorly understood. In the present study, we evaluated the mechanism of resistance to the BET inhibitor I-BET151 and its signaling pathway to overcome resistance in U937 cells. Treatment with 10 μM I-BET151 significantly induced growth inhibition, apoptosis, and cell cycle modulation, including increases in sub-G1 and G1 phases and decreases in S and G2/M phases, in U937 cells. However, no significant changes in these factors were detected in I-BET151-resistant U937 (U937R) cells. Combined treatment with I-BET151 and IKK inhibitor VII synergistically induced apoptosis in U937 and U937R cells. Increased expression of bromodomain-containing protein (BRD) 2, BRD4, and nuclear NF-κBp65 proteins was detected in U937R cells. IKK inhibitor VII inhibited the activation of NF-κBp65 protein in the nuclear fraction of U937R cells. These findings suggest that resistance to I-BET151 in U937R cells is related to constitutive activation of the NF-κB signaling pathway via increased expression of both BRD2 and BRD4. Targeting the NF-κB signaling pathway may be an effective therapeutic strategy to enhance or restore the sensitivity to I-BET151 in U937 cells.